Corporate Walkout Decisions and the Value of Default - Dahlström, Tom; Mella-Barral, Pierre (Review of Finance, 2003)
Abstract We present a continuous-time asset pricing model of the levered firm where shareholders select not only the timing but also the form of abandonment. Shareholders can walk out of the firm either by (i) defaulting on their debt obligations or (ii) selling their shares to alternative operators of, the technologies, as in a corporation sale . The structural model relates shareholders' ex-post choice to both technological and financial factors. Considering that operators' technological supremacy is not universal, we obtain that whereas default necessarily involves an inefficient timing of ownership transfer, corporation sales do not. Then, the likelihood of default being chosen instead of a corporation sale increases with (i) the degree of leverage displayed by the firm and (ii) its technological supremacy. By ignoring corporation sales, existing defaultable bond pricing models have thus a tendency to exaggerate risk premia and underestimate the borrowing ability (debt capacity) of firms.